Exploring the background conditions for playing sports of pre-school children - Szépné Varga, Henrietta; Balatoni, Ildikó (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2018)
The objective of kindergarten education is to satisfy the psychosomatic needs of preschoolers. It is important that children are provided with the opportunity to be physically active. In the research, authors were interested in whether the necessary infrastructure and other requirements were provided to achieve this goal. The survey was conducted in the spring of 2018 in the kindergartens of Debrecen and Hajdú-Bihar County. Authors were keen to find out how many and what size gyms were available for children. The analyses how much time children spent in the open air and asked what other afternoon sessions were held in kindergartens. We need to teach our children the love of physical activity and kindergartens play a decisive role in this process. The survey reveals that there are big differences in the relevant infrastructure; however, institutions involved in the present study seek to meet the children’s need for physical activity according to their capabilities.